The impact of intellectual capital on dynamic innovation performance: An overview of research methodology - Mostafa A. Ali; Nazimah Hussin; Hossam Haddad; Nidal Mahmoud Al-Ramahi; Tareq Hammad Al-Mubaydeen; Ibtihal A. Abed (Journal of Risk and Financial Management, 2022)
Research technique is a critical component of every study, and, therefore, determining the method of research is a crucial step in that process. This paper serves as an introduction to the design of an investigation method for the impacts of intellectual capital on dynamic innovation performance. It discussed the research paradigm from a wide context encompassing various domains mentioned in the literature. Subsequently, the validity, accuracy, and advantages of the chosen research instrument were thoroughly discussed, from the questionnaire's design and structure through the final stage of analysis for all variables. Three sections of this paper encompassed the explanations of the procedures for sampling design that had been set up to achieve the proposed research objectives. In addition, trustworthiness was acquired through deploying experts and piloting the method throughout an experimental context. The procedures of data collection and data cleaning had been presented. Finally, the last two sections emphasized the data analysis and moderator procedures in the present research methodological context.
Keywords: 650; research design; research instrument; sampling design; validity and reliability; data collection procedures; data cleaning; data analysis procedures